Czy Prezydent Rzeczypospolitej Polskiej jest pracownikiem? Analiza zawodowego statusu głowy państwa w świetle art. 22 Kodeksu pracy - Kazimierski, Damian (Studia Prawa Publicznego, 2025)
The President of the Republic of Poland holds a unique role in the Polish constitutional order, and is called the most important person in the state. In connection with being the head of state, the president carries out tasks within the framework of a certain type of employment, the assessment of which in the light of labour law is the task of this publication. The fulﬁlment of the features of the employment relationship expressed in Article 22 of the Labour Code (Kodeks pracy) is considered as the most important criterion, and the assessment of their validity in the context of the type of the President’s employment is the subject of the following sections of the article. While some of the prerequisites prima facie appear to be fulﬁlled (receiving a salary, performing a job), others may pose problems for the researcher. Undoubtedly, the greatest of these is the identiﬁcation of the president’s subordination within his or her possible employment relationship. By examining the constitutional position and its impact on the personal status of the person, as well as by comparing the president’s position to that of the members of the organs of corporations, the author concludes that it is not impossible to consider the president an employee. Referring to the jurisprudence concerning CEOs of companies and persons managing public authorities, the publication posits that the president’s employer would be his or her auxiliary apparatus in the form of the Chancellery of the President of the Republic (Kancelaria Prezydenta RP). The ﬁnal paragraphs of the text present selected cases of the employee nature of the president’s status in other countries – France, the United States and Brazil.